Optical Coherence Tomography Angiography Biomarkers of Retinal Thickness and Microvascular Alterations in Sjogren's Syndrome - Liu, Ren; Wang, Yan; Li, Qiuyu; Xia, Qiang; Xu, Tian; Han, Ting; Cai, Shuang; Luo, Shuilin; Wu, Rui; Shao, Yi (Frontiers in Neurology, 2022)
Purpose To investigate the differences of retinal thickness (RT) and superficial vascular density (SVD) between patients with Sjogren's syndrome (SS) and healthy controls (HCs) using optical coherence tomography angiography (OCTA). Methods Individuals with SS and healthy controls were enrolled (n = 12 per group). An en-face OCTA scan was performed on each eye. Images were segmented into 9 subregions and macular RT and SVD were measured and compared between the 2 groups. Results Visual acuity (VA) differed significantly between patients with SS (24 eyes) and controls (24 eyes) (p < 0.001). In patients with SS, inner RT was reduced in the inner superior region, outer RT was reduced in the outer nasal (ON) region, and full RT was reduced in the ON region compared with the control group (p < 0.05). RT was negatively correlated with serum IgG level in the outer and full retina at ON regions (p < 0.05). SVD in the inner nasal, ON, and inner temporal regions was significantly lower in patients with SS than in control subjects (p < 0.05). SVD was positively correlated with full RT in the ON region in patients with SS (p < 0.05). The areas under the receiver operating characteristic (ROC) curves for the diagnostic sensitivity of outer RT and full RT in the ON region for SS were 0.828 (95% CI: 0.709–0.947) and 0.839 (95% CI: 0.715–0.963), respectively. Conclusions In patients with SS, retinal thinning in the macular area—which affects vision—can also reflect the severity of dry eyes in SS and has clinical value for assisted imaging diagnosis.